Pengaruh Indonesia Port Corporation (IPC) dan Kompetensi Terhadap Dwelling Time di Moderasi Oleh Peran Bea Cukai Studi Pada Pelabuhan Tanjung Priok - Catarina Cori Paramitha; Jimmy Prahesha Sugandi (JOURNAL FOR BUSINESS AND ENTREPRENEURSHIP, 2019)
This research is a study of "The role of the IPC role and competency in residence time is moderated by the role of customs and excise. While the independent variables in research are the role of IPC and competence. The data used in this study are primary data obtained from questionnaire research. This study transferred the questionnaire to 300 respondents in Tanjung Priok port. All questionnaires that returned only 98 and filled in completely can be used as research data. The study was conducted with several stages. The first stage is to explore theories from libraries and collect data from researched objects. The second stage is collecting primary data through questionnaire research. The third stage is to test the feasibility of the data by using the validity test and reliability test. The fourth stage is the stage of testing the research hypothesis. The results of the study prove the fact that the partial role of IP determines positively and is significant for residence time. Positive competence and significant time to stay. The role of customs and excise affects negatively and not significantly. Moderating the role of customs and excise can weaken the role of the IPC in terms of residence time. Moderation of the role of customs is able to complement positive and insignificant competencies.Keywords: Dwelling Time, Role of Customs and Excise, Competence, Role of IPC